Overview of the application of ecological concrete in sponge city construction - Wang, Lei; Liu, Zhikui; Yan, Yan; Li, Shengdong; Xie, Yongxiong (Frontiers in Earth Science, 2023)
As a prominent component of the construction field of sponge cities, ecological concrete is an essential tool to reach the goals of green, low-carbon living and sustainable development. A quantitative summary of the preliminary research on ecological concrete infrastructure in sponge city architecture is needed. Therefore, CiteSpace and VOSviewer were applied to perform a comparative analysis of the number of papers, countries, institutions, core authors, literature co-citations, research hotspots, and future trends in ecological concrete in the sponge city construction industry. The results show that the number of papers on ecological concrete is increasing, the research collaboration between domestic and foreign authors is relatively single, and there is insufficient interdisciplinary integration between institutions and the phenomenon of "relatively independent research." The number of papers published in the field of ecological concrete construction has been on the rise, reaching more than 100 in each of the last ten years, with China and the United States contributing more to the scientific output of the field. To meet the needs of global environmental protection and resource conservation, the theme of "promoting comprehensive resource conservation and recycling" will continue in the future, making concrete a feature of green, low-carbon, sustainable development and other areas of environmental protection in the construction field.